Whisperings from the Corridors Stories of Teachers in Higher Education - Garvis, Susanne; Dwyer, Rachael; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
This book is intended to illuminate the experiences of teachers working in higher education, the tensions they face in working in an increasingly complex professional landscape. Higher teaching loads, increased expectations of research output, and changing social and economic structures that shape the way students view their tertiary education have a profound affect on university teachers$1 (Bwork. The pages of this volume are filled with the stories of teachers in universities that allow the reader to look deeply into the complexities of their work. We and the other authors do not pretend that the stories told here are representative of all university teachers, that they are in any way generalisable, but that others may learn from the knowledge that is shared.s
Keywords: Education; Education; Education (general).